Miniature Autonomy as Means to Find New Approaches in Reliable Autonomous Driving AI Method Design - Tiedemann, Tim; Schwalb, Luk; Kasten, Markus; Grotkasten, Robin; Pareigis, Stephan (Frontiers in Neurorobotics, 2022)
AI methods need to be evaluated thoroughly to ensure a reliable behavior. In applications like autonomous driving, a complex environment with an uncountable number of differing situations and conditions needs to be handled by a method whose behavior needs to be predictable. To accomplish this, simulations can be used as a first step. However, the physical world behaves different, as the example of autonomous driving shows. There, erroneous behavior has been found in test drives that was not noticed in simulations as the errors were caused by conditions or situations that were not covered by the simulations. However, the problem with real world testing of autonomous driving features is that critical conditions or situations occur very rarely – while the test effort is high. A solution can be the combination of physical world tests and simulations – and miniature vehicles as an intermediate step between both. With model cars (in a sufficiently complex model environment) advantages of both can be combined: (1) low test effort and a repeatable variation of conditions/situations as an advantage like in simulations and (2) (limited) physical world testing with unspecified and potentially unknown properties as an advantage like in real-world tests. Additionally, such physical tests can be carried out in less stable cases like already in early stages of AI method testing and/or in approaches using online learning. Now, we propose to use a) miniature vehicles at a small scale of 1:87 and b) to use sensors and computational power only on the vehicle itself. By this limitation a further consequence is expected: Here, autonomy methods need to be optimized drastically or even redesigned from scratch. The resulting methods are supposed to be less complex – and, thus, again less error-prone. We call this approach “Miniature Autonomy” and apply it to road, water, and aerial vehicles. In this paper, we briefly describe a small test area we built (3 sqm.), a large test area used alternatively (1,545 sqm.), two last generation autonomous miniature vehicles (one road, one aerial vehicle), and an autonomous driving demonstrating application.